Self-Construal: Perceptions of Work and School in Two Generations of Hmong Immigrants - Pa Der Vang (Hmong Studies Journal, 2020)
This paper describes a research project in which 40 Hmong participants were interviewed comparing two generations of Hmong immigrants. Self-construal served as an operating framework in understanding respondent satisfaction with work and school; two very salient features in individual functioning and worldview. Self-construal is the manner in which the client views themselves in relation to others and is influenced by culture. The researcher compared perceptions of work and school among first and generation immigrants in terms of work in relation to self-construal. The study of self-construal is important for social workers and other service providers who work with immigrants and refugees as it informs cross cultural practice. Understanding culturally informed views on client satisfaction and perceptions will help social workers gain a stronger understanding of the client experience and work cross culturally with clients.